2018
DOI: 10.3389/fimmu.2018.02469
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Germinal Center Response

Abstract: The germinal center (GC) is a specialized microstructure that forms in secondary lymphoid tissues, producing long-lived antibody secreting plasma cells and memory B cells, which can provide protection against reinfection. Within the GC, B cells undergo somatic mutation of the genes encoding their B cell receptors which, following successful selection, can lead to the emergence of B cell clones that bind antigen with high affinity. However, this mutation process can also be dangerous, as it can create autoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
212
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 167 publications
2
212
0
1
Order By: Relevance
“…The generation of lasting protective immunity requires the production of long-lived plasma cells that secrete high affinity class-switched antibodies 6 . Plasma cells are the ultimate output of the germinal center (GC), a specialized immune response that forms in secondary lymphoid organs 7 . The GC reaction requires the concerted efforts of many different cell types that must be coordinated in time and space: B cells, T follicular helper (Tfh) cells, dendritic cells and macrophages are brought together upon a network of specialized stromal cells that provide migratory cues that direct cells to, and within, the GC 8 .The GC is a polarized structure with two functionally distinct compartments known as light and dark zones 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of lasting protective immunity requires the production of long-lived plasma cells that secrete high affinity class-switched antibodies 6 . Plasma cells are the ultimate output of the germinal center (GC), a specialized immune response that forms in secondary lymphoid organs 7 . The GC reaction requires the concerted efforts of many different cell types that must be coordinated in time and space: B cells, T follicular helper (Tfh) cells, dendritic cells and macrophages are brought together upon a network of specialized stromal cells that provide migratory cues that direct cells to, and within, the GC 8 .The GC is a polarized structure with two functionally distinct compartments known as light and dark zones 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…To do this, GC B cells move to the light zone where they can receive help from a specialized subset of CD4 + T cells, Tfh cells 11 . GC B cells that received help from Tfh cells then migrate back to the dark zone and either undergo further rounds of proliferation and mutation or differentiate into memory B cells or long-lived antibody-secreting cells that exit the GC 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The CXCR4-CXCL12 interaction is of central importance in the GC reaction (23, 27, 28), and we have previously shown that ARHGAP25 regulates the strength of response to CXCR4 signaling in hematopoietic stem and progenitor cells (21). Furthermore, CXCL12 is highly expressed in the GC DZ, where we found more B cells in Arhgap25 -/- mice.…”
Section: Resultsmentioning
confidence: 99%
“…The GC reaction plays an important role in humoral immunity, as B-cells with the highest affinity to GC-contained antigens are selected to become plasma cells that produce high-affinity antibodies or memory B-cells [72][73][74]. GCs are formed in secondary lymphoid organs at different time points.…”
Section: γδ T-cells and Germinal Centersmentioning
confidence: 99%